Four-point bending test to evaluate sulphide stress cracking using sodium thiosulfate - Sapanathan, Thaneshan; Samusawa, Itaru; Al Helal, Ammar; Shimamura, J. (2024)
Sulfide Stress Corrosion (SSC) is a complex environmental assisted cracking phenomenon and it causes trench formation due to localised corrosion perpendicular to the load axis under external loading. Due to the high toxicity and flammable effect of H2S gas, it requires sophisticated instruments and dedicated laboratory facility to study the SSC. Thus a few specialised laboratories around the world can handle the H2S and perform SSC studies safely. As a relatively safe alternative, in 1993, Tsujikawa et al proposed to use thiosulphate (S2O32-) for studying SSC in low alloy steel, stainless steel and corrosion resistance alloys (CRAs). Later many researchers expanded the knowledge of SSC using thiosulphate to study the fundamentals and claimed the effect of different alloys under the exposure of simulated H2S. In this study, we used the four-point bend test to evaluate SSC in thiosulfate environment with an inline monitoring of H2S production for the first time. This system was designed for atmospheric pressure, to study SSC with a leak proof flow line. Our extreme lab facility with added safety features enable to conduct the SSC experiments safely and confidently. Using this sophisticated setup, we have evaluated the SSC susceptibility for various steels and validated the S2O32- test condition comparing to the use of H2S gas using pit/trench morphologies. FeS was mainly identified in corrosion product using X-ray direction in both tests with H2S gas and simulated S2O32- test conditions.